(untitled) (Iraqi Journal of Medical Sciences, 2021)
Background: The fibroblast growth factor receptors (FGFRs) family includes five tyrosine kinase receptors, which play an important role in many cellular mechanisms including proliferation, migration and survival. Deregulations in the genes that coding for these receptors, mainly the FGFR3 gene, had been reported in patients with urothelial carcinoma of the urinary bladder. Objective: To estimate the frequency of FGFR3 gene amplification in patients with urothelial carcinoma of the urinary bladder and its relation to some clinico-pathological parameters of the tumor. Methods: The present retrospective study included 30 paraffin blocks of urothelial carcinoma tissue (trans-urethral resection of bladder tumor (TURBT)), and 10 samples of normal bladder tissue (control group). Sections were taken from each paraffin block for studying FGFR3 gene amplification by fluorescent in situ hybridization (FISH) technique. Results: FGFR3 gene was shown to be amplified in 4 (13.3%) out of 30 urothelial carcinoma cases. There was significant relation between FGFR3 gene amplification and tumor’s pathological stage (p=0.037). FGFR3 gene wasn’t statistically correlated with the patient’s age, gender, tumor’s grade or the lympho-vascular permeation. Conclusion: FGFR3 gene amplification was detected in 13.3% of urothelial carcinoma of the urinary bladder cases, which may reflect its role in carcinogenesis process. This amplification was statically correlated to tumor’s pathological stage suggesting its relation to tumor progression. Keywords: FGFR3, FISH, TURBT, urothelial carcinoma, gene amplification Citation: Al-Marashi MA, Qasim BJ. Fibroblast Growth Factor Receptor 3 (FGFR3) gene amplification in patients with urothelial carcinoma of the urinary bladder.Iraqi JMS. 2021; 19(1): 116-125. doi: 10.22578/IJMS.19.1.15